2020
DOI: 10.1139/apnm-2020-0058
|View full text |Cite
|
Sign up to set email alerts
|

Growing up strong: The importance of physical, mental, and emotional strength during childhood and adolescence with focus on dietary factors

Abstract: Childhood and adolescence are critical time periods for growth and development. Given the current physical and psychological health concerns affecting U.S. youth, an emerging area of interest exists supporting the importance of physical and psychological aspects of strength for health, resilience, and well-being through these life stages. This synopsis highlights the key concepts that were presented within the 2018 Strength Summit conference entitled, The Role of Strength in Optimal Health and Well-be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 87 publications
(138 reference statements)
0
6
0
Order By: Relevance
“…Rather, ‘blinded’ weigh-ins, in which adolescents stand with their backs to the numerical display of weight, may prevent the possibly triggering effect of seeing one's weight and becoming distressed. Providers should openly discuss how differences in their patients’ bodies are affected by pubertal changes, and as such, conversations about puberty and growth should emphasize the normalcy of weight gain during adolescence [1,2,4 ▪▪ ]. Providers may find it helpful to show adolescents’ placement on a growth chart, rather than indicating they have a ‘normal’ or ‘bad’ BMI, to emphasize the dynamics of weight change and growth at this stage.…”
Section: Recommendations For Adolescent Carementioning
confidence: 99%
See 1 more Smart Citation
“…Rather, ‘blinded’ weigh-ins, in which adolescents stand with their backs to the numerical display of weight, may prevent the possibly triggering effect of seeing one's weight and becoming distressed. Providers should openly discuss how differences in their patients’ bodies are affected by pubertal changes, and as such, conversations about puberty and growth should emphasize the normalcy of weight gain during adolescence [1,2,4 ▪▪ ]. Providers may find it helpful to show adolescents’ placement on a growth chart, rather than indicating they have a ‘normal’ or ‘bad’ BMI, to emphasize the dynamics of weight change and growth at this stage.…”
Section: Recommendations For Adolescent Carementioning
confidence: 99%
“…Adolescence is a formative period of development when foundational messages regarding nutrition and body image take root [1,2]. The physical and psychological changes that occur in this period make adolescents especially vulnerable to disordered eating and body image concerns [1,3].…”
Section: Introductionmentioning
confidence: 99%
“…Childhood and adolescence are critical stages of human development, where rapid physical, mental, and social changes occur [1]. During these formative years, individuals engage in various lifestyle behaviours and form habits contributing to their overall physical and mental health [2, 3]. Previous evidence has shown that healthy lifestyle habits, characterised by adequate physical activity (PA) [4], reduced sedentary behaviour (SB) [5], and optimal sleep [6] developed during childhood and adolescence, can persist into adulthood.…”
Section: Introductionmentioning
confidence: 99%
“…Childhood is a crucial period of growth and development [ 19 ]. Entering primary school, children markedly change their lifestyle.…”
Section: Introductionmentioning
confidence: 99%